2010
DOI: 10.1017/s1431927610000279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blue Light on the Leaf Morphoanatomy ofIn Vitro Kalanchoe pinnata(Lamarck) Persoon (Crassulaceae)

Abstract: Kalanchoe pinnata (Lamarck) Persoon (Crassulaceae) (air plant, miracle leaf) is popularly used to treat gastrointestinal disorders and wounds. Recently, the species was tested to treat cutaneous leishmaniasis with successful results. This medicinal activity was associated with the phenolic fraction of the plant. Blue light induces biosynthesis of phenolic compounds and many changes in anatomical characteristics. We studied the effects of supplementary blue light on the leaf morphology of in vitro K. pinnata. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The results of the present study also showed that, compared with monochromatic red light, the accumulation of 3,4-dihydroxybenzoic acid, gallic acid, and ferulic acid in P. cynaroides plantlets was enhanced by the presence of blue light, whether individually or in combination with red light (red + blue LEDs) ( Table 2). This is in agreement with studies that showed that blue light stimulates the biosynthesis of phenolic compounds in plants (Leal-Costa et al, 2010;Meng et al, 2004;Rao and Ravishankar, 2002;Saleh, 2007). Similarly, chlorogenic acid in lettuce seedlings grown under blue-containing LEDs was also higher than those irradiated by red lights (Johkan et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…The results of the present study also showed that, compared with monochromatic red light, the accumulation of 3,4-dihydroxybenzoic acid, gallic acid, and ferulic acid in P. cynaroides plantlets was enhanced by the presence of blue light, whether individually or in combination with red light (red + blue LEDs) ( Table 2). This is in agreement with studies that showed that blue light stimulates the biosynthesis of phenolic compounds in plants (Leal-Costa et al, 2010;Meng et al, 2004;Rao and Ravishankar, 2002;Saleh, 2007). Similarly, chlorogenic acid in lettuce seedlings grown under blue-containing LEDs was also higher than those irradiated by red lights (Johkan et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…In a previous study, the production of phenolic compounds increased in K. pinnata grown in vitro under supplemental blue light (Leal-Costa et al, 2010).…”
Section: Microchemical Testsmentioning
confidence: 78%
“…Some anatomical studies have examined K. pinnata (Jain et al 2008;Anjoo & Kumar, 2010;Leal-Costa et al 2010) and K. crenata (Hyakutake & Grotta, 1972). However, these studies provided neither information about the influence of environmental light intensity on the leaf anatomy of these species, nor a detailed anatomical description of them.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed the presence of phenolic-producing cells located in the mesophyll of Inula viscosa (L.) Aiton leaves (Nikolakaki and Christodoulakis 2004) as well as Crassula multicava Lem. (Castro and Demarco 2008) and several Kalanchoë species (Leal-Costa et al 2010;Moreira et al 2012;Chernetskyy et al 2018). Different classes of phenolic compounds serve different functions.…”
Section: Discussionmentioning
confidence: 99%